A Critical Review of Bangladesh's Child Labor Regulations and Policies - Md Mahmudul Hoque (World Development Sustainability)
Child labor remains widespread in Bangladesh. The country has ratified the UN Convention on the Rights of the Child, the ILO's Minimum Age Convention, and the Worst Forms of Child Labor Convention. The government has developed a legal and policy framework to eliminate all forms of child labor by 2025. This paper examines the country's pertinent national regulations, policies, and programs to identify discrepancies and gaps. The author appraised a variety of government documents, including laws, rules, policies, and reports, as well as emerging evidence. The results indicate that the country's legal and policy framework is comprehensive and well-aligned with its long-term development plans. Institutional bodies collaborate to implement and monitor these policies and programs designed to reduce child labor. Nonetheless, a few significant gaps render the framework insufficient, inconsistent, and ineffective. The government has not yet ratified several important conventions. The application of the Labor Act of 2006 is primarily restricted to the formal sectors, whereas most of the hazardous child labor occurs in the informal agricultural and domestic work sectors. In many cases, the absence of birth registration documents renders the determination of a child's age arbitrary. Emerging evidence suggests that the COVID-19 pandemic has exacerbated the situation and that dangerous child labor is on the rise in urban areas. However, the current framework lacks legal provisions regarding hazardous child labor, and government support programs are inadequate. The government must review its policies and develop programs in collaboration with communities to protect children's best interests.